2017
DOI: 10.1038/s41467-017-00229-9
|View full text |Cite
|
Sign up to set email alerts
|

Seismological evidence for a localized mushy zone at the Earth’s inner core boundary

Abstract: Although existence of a mushy zone in the Earth’s inner core has been hypothesized several decades ago, no seismic evidence has ever been reported. Based on waveform modeling of seismic compressional waves that are reflected off the Earth’s inner core boundary, here we present seismic evidence for a localized 4–8 km thick zone across the inner core boundary beneath southwest Okhotsk Sea with seismic properties intermediate between those of the inner and outer core and of a mushy zone. Such a localized mushy zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…This is in agreement with previous studies which found complexity beneath the Pacific Ocean (Stroujkova and Cormier, 2004;Miller et al, 2013;Cormier, 2015;Irving and Deuss, 2015;Yu et al, 2017). The inner core boundary beneath the northern Pacific Ocean is also found to display small scale features including topography and melting (Waszek and Deuss, 2015;Tian and Wen, 2017;Shen et al, 2016).…”
Section: Velocity Structuresupporting
confidence: 82%
See 2 more Smart Citations
“…This is in agreement with previous studies which found complexity beneath the Pacific Ocean (Stroujkova and Cormier, 2004;Miller et al, 2013;Cormier, 2015;Irving and Deuss, 2015;Yu et al, 2017). The inner core boundary beneath the northern Pacific Ocean is also found to display small scale features including topography and melting (Waszek and Deuss, 2015;Tian and Wen, 2017;Shen et al, 2016).…”
Section: Velocity Structuresupporting
confidence: 82%
“…Alternatively, the observations may result from the inner core hemispheres, whereby the deeper ray paths spend more time in the low velocity west hemisphere, and latitudinal variation in the hemisphere boundary is reported (Cormier, 2015;Irving and Deuss, 2015;Yu et al, 2017). The lower velocity we detect in the northern part of our dataset may correspond to small scale mushy zones on the inner core boundary observed here (Tian and Wen, 2017;Shen et al, 2016).…”
Section: Velocity Modelmentioning
confidence: 49%
See 1 more Smart Citation
“…They proposed a model of mosaic ICB structure, in which regions having a liquid-liquid transition are interspersed with those having a liquid-solid transition. Lateral variations observed in PKiKP/PcP amplitude ratios and PKiKP-PcP travel times, as well as complexity observed in precritical PKiKP waveforms, might also support the presence of such a complex ICB structure (Tian & Wen, 2017;Waszek & Deuss, 2015). Seismic and thermodynamic modeling constrains the thickness of transition patches as described by Krasnoshchekov et al (2005) to less than 10 km (Cummins & Johnson, 1988b;Deguen et al, 2007;Tian & Wen, 2017).…”
Section: 1029/2018gc007562mentioning
confidence: 99%
“…At the Earth's radii of about 1,220 km, the temperature falls below the solidus of the Fe‐Ni alloy of the outer core (OC) and IC freezes (Jacobs, ). The up‐to‐date description of this outward crystallization is very far from complete and admits a number of scenarios including formation of slurry, dendritic, and non‐dendritic morphologies (e.g., Fearn et al, ; Loper & Roberts, ; Tian & Wen, ). It was shown that interfacial heat flux at either boundary of the OC has a significant effect on solidification regime and IC texture formation, so the cooling rate during phase transition is not uniform throughout the inner core boundary (ICB) and may give rise to multi‐scale heterogeneities (e.g., Aubert et al, ; Gubbins et al, ).…”
Section: Introductionmentioning
confidence: 99%